Frequency and geographic distribution of TERT promoter mutations in primary hepatocellular carcinoma - Pezzuto, Francesca; Buonaguro, Luigi; Buonaguro, Franco M.; Tornesello, Maria Lina (Infectious agents and cancer, 2017)
Primary hepatocellular carcinoma (HCC) mainly develops in subjects chronically infected with hepatitis B (HBV) and C (HCV) viruses through a multistep process characterized by the accumulation of genetic alterations in the human genome. Nucleotide changes in coding regions (i.e. TP53, CTNNB1, ARID1A and ARID2) as well as in non-coding regions (i.e. TERT promoter) are considered cancer drivers for HCC development with variable frequencies in different geographic regions depending on the etiology and environmental factors. Recurrent hot spot mutations in TERT promoter (G > A at-124 bp; G > A at −146 bp), have shown to be common events in many tumor types including HCC and to up regulate the expression of telomerases. We performed a comprehensive review of the literature evaluating the differential distribution of TERT promoter mutations in 1939 primary HCC from four continents. Mutation rates were found higher in Europe (56.6%) and Africa (53.3%) than America (40%) and Asia (42.5%). In addition, HCV-related HCC were more frequently mutated (44.8% in US and 69.7% in Asia) than HBV-related HCC (21.4% in US and 45.5% in Africa). HCC cases associated to factors other than hepatitis viruses are also frequently mutated in TERT promoter (43.6%, 52.6% and 57.7% in USA, Asia and Europe, respectively). These results support a major role for telomere elongation in HCV-related and non-viral related hepatic carcinogenesis and suggest that TERT promoter mutations could represent a candidate biomarker for the early detection of liver cancer in subjects with HCV infection or with metabolic liver diseases.